Pharmacosimilars In Obesity Medicine: Informed Choice, Appropriate Choice - Sanjay Kalra; Amandeep Singh; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Newer development in endocrine pharmacology have blurred the distinction between biosimilars and generics. The originator semaglutide, for example, is a biologically active compound, but later versions are chemically synthesized generics. Tirzepatide is a synthetic polypeptide. These molecules are marketed in different strengths and delivery devices across the world. The word ‘pharmaco-similar’ can be used to describe both biosimilar and generic versions of originator peptidebased medications. This communication suggests a useful framework which assists in sharing information and reaching an informed decision regarding choice of anti-obesity medication. This approval process and status, evidence and experience base, economic factors, rules related to interchange/substitution, robustness of cold chain, and availability of uninterrupted supply all influence this decision. Keywords: Biosimilar, diabetes, generic, GIPRA, GLP1RA, liraglutide, obesity, semaglutide, tirzepatide